Training for parents of adolescents: Learning behavioral concepts and parenting practice to act in teenagers (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
The present study aims to present the results of training for teenager’s parents. Data collection was from appraisal with two groups, an experimental one and a control one. Interviews, pre and after-tests, were performed using semi-structured questionnaire with 12 parents and with their children, with 15 people as total. Eight structured daily sessions, all composing this training in which are discussed parenting practices appropriate to deal with teens. After the interventions, it was verified, meaningful changes related to the training, and those changes were identified in parents and teenagers also. It was concluded that training for parents of teens is a valid measure of intervention to promote healthier environments for the development of teenagers children.
Keywords: adolescence; parental training; parenting practices